The dancing master - Klassen, Julie, 1964- (Bethany House, a division of Baker Publishing Group, 2013)
"Regency era dancing master Alec Valcourt wants to bring new life to the sleepy little village of Beaworthy in remote Devonshire--and to one young woman's restless heart"--